Factor structure and psychometric properties of the Chinese version of the Odor Awareness Scale - Zhang, Binfeng; Li, Xiuxia; Tan, Peixuan; Liu, Yuxing; He, Wanyong; Wang, Lu; Huang, Shuling; Nie, Guanghui (Frontiers in Psychiatry, 2023)
The Odor Awareness Scale (OAS) is a questionnaire that assesses individual differences in awareness of odors in the surrounding environment, which has been shown to be associated with affective symptoms in recent researches. To further research, A Chinese version of the OAS needs to be introduced. Objective: To investigate the factor structure and validate the psychometric properties of the OAS. Methods: A total of 978 participants from college were randomly allocated into two groups for exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), respectively. Additionally, the study entailed item analysis and scrutinized internal consistency reliability, test-retest reliability, and concurrent validity. Test-retest reliability was assessed by having 214 participants complete the OAS twice at a oneweek interval. Concurrent validity was measured using the Body Odor Sniffing Questionnaire (BOSQ), the Generalized Anxiety Disorder Scale (GAD-7), and the Toronto Alexithymia Scale (TAS-20). Results: EFA identified three factors that best fit the data: odor sensitivity, odor impact, and odor attention. CFA validated a second-order factor model, yielding good fit indices: 𝜒 2 /𝐷𝑓 = 2.326, RMSEA = 0.052, CFI = 0.911, TLI = 0.900, SRMR = 0.053. The final version of the OAS comprised 27 items and exhibited a commendable internal consistency reliability (Cronbach's α = 0.913), and a good test-retest reliability, as evidenced by the high Pearson correlation coefficient (r = 0.940) and intraclass correlation coefficient (ICC = 0.940). The OAS was significantly correlated with BOSQ (r = 0.416), GAD-7 (r = 0.115) and TAS-20 (r = -0.081).The Chinese version of the OAS demonstrated robust reliability and validity, rendering it a valuable instrument for evaluating odor awareness in the Chinese population.